2013
DOI: 10.1179/1743281212y.0000000077
|View full text |Cite
|
Sign up to set email alerts
|

Research on stamp charging car coal box pressure through field test

Abstract: Coal box pressure has great significance in stamp charging car design. Because of the complexity of the dynamic constitutive relation of the coal powder, the pressure is usually considered in the design as a linear load, which presents neither the instantaneous maximum impact nor the variation during the stamping process, and therefore lacks accuracy. In this research, to obtain a more accurate box pressure, a series of field tests have been conducted, which included side wall tests, bottom plate tests and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Also presented are the numerical solutions of stress increment to the partial differential equations of the DKM model. Comparing to the earlier test results, 8 the simulating result has indicated that the DKM model can provide accurately the stamping pressure curves as well as other information for the charging car designers and reveal some inherent behaviours of the coal cake.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Also presented are the numerical solutions of stress increment to the partial differential equations of the DKM model. Comparing to the earlier test results, 8 the simulating result has indicated that the DKM model can provide accurately the stamping pressure curves as well as other information for the charging car designers and reveal some inherent behaviours of the coal cake.…”
Section: Introductionmentioning
confidence: 60%
“…Gravity was involved in the process. According to the earlier field test, 8 the lifting height of stamper is set to 0·5 m, which means that the stamper’s initial velocity is v Y = −3·13 m s −1 . The process was divided into a sequence of three stages: initial set-up, gravity equilibrium and stamping impact.…”
Section: Calculation With Dkm Modelmentioning
confidence: 99%
See 1 more Smart Citation